CULTURAL AWARENESS: MEMAHAMI SENSITIVITAS MULTIKULTURAL DALAM PRAKTIK KONSELING DI SEKOLAH - Putri, Marsha Hariani; Nadhirah, Nadia Aulia; Budiman, Nandang (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2024)
Abstract: The counseling process in school environments is vulnerable to cultural bias challenges that can impede its effectiveness. A multicultural or cross-cultural counseling approach is crucial for understanding counselees from diverse backgrounds. This study aims to explore the level of cultural understanding and awareness among Guidance and Counseling Teachers towards multicultural counseling in schools, as well as their ability to form effective relationships with students from various cultural backgrounds. Utilizing the Systematic Literature Review (SLR) method, this research examines 47 relevant journal articles from Google Scholar published within the last 5 to 10 years, yielding five key articles that underscore the importance of cultural awareness and competence development to enhance counseling effectiveness. The findings reveal significant variations in cultural awareness among guidance counselors, identifying an urgent need for skill development and intervention strategies to address challenges such as counselor encapsulation and cross-cultural communication barriers. Initiatives such as the development of service models, training modules, and competence enhancement programs have proven effective in strengthening cultural awareness and counseling capabilities. In conclusion, a deep understanding of cultural awareness and multicultural competencies is not only essential for effective interaction between counselors and students but also crucial in advancing inclusive education that embraces cultural diversity. Abstrak: Proses konseling di lingkungan sekolah rentan terhadap tantangan bias budaya yang dapat menghambat efektivitasnya. Pendekatan konseling multikultural atau lintas budaya penting untuk memahami konseli dari berbagai latar belakang. Penelitian ini bertujuan untuk mengeksplorasi tingkat pemahaman dan kesadaran budaya Guru Bimbingan dan Konseling terhadap konseling multikultural di sekolah, serta kemampuan mereka membentuk hubungan efektif dengan siswa dari latar belakang budaya yang beragam. Menggunakan metode Systematic Literature Review (SLR), penelitian ini menelaah 47 artikel jurnal relevan dari Google Scholar yang diterbitkan dalam rentang waktu 5 sampai 10 tahun terakhir, menghasilkan lima artikel kunci yang menegaskan pentingnya kesadaran budaya dan pengembangan kompetensi untuk meningkatkan efektivitas konseling. Hasil penelitian menunjukkan adanya variasi signifikan dalam tingkat kesadaran budaya di antara guru BK, mengidentifikasi kebutuhan mendesak untuk pengembangan keterampilan dan strategi intervensi yang dapat mengatasi tantangan seperti enkapsulasi konselor dan hambatan komunikasi lintas budaya. Inisiatif seperti pengembangan model layanan, modul pelatihan, dan program peningkatan kompetensi terbukti efektif dalam memperkuat kesadaran budaya dan kemampuan konseling. Kesimpulannya, pemahaman mendalam tentang kesadaran budaya dan kompetensi multikultural tidak hanya esensial untuk interaksi efektif antara konselor dan siswa tetapi juga krusial dalam memajukan pendidikan inklusif yang merangkul keragaman budaya.